Development of vitamin e-enriched nanoemulsion for wound healing - Chong, Wai Ting (2020)
Wound problem is a global health care issue that can burden the individuals and countries. Vitamin E is a potent natural antioxidant and tocopherols are the common form to be used in skin-care products. However, studies found that the antioxidant potency of tocotrienols is 60 times than tocopherols which believe can benefit for the wound problems. Red palm oil (RPO) rich in vitamin E (70-80% tocotrienols; 20-10% tocopherols) and carotenoids, is a favourable choice to be used as a natural source of tocotrienols. In our work, a tocotrienol-rich oil-in-water-nanoemulsion (NE) formulation was optimized using response surface methodology (RSM) and formulated using high- pressure homogenizer. Effect of the concentration of three independent variables [surfactant (5-15 wt%), co-solvent (10-30 wt%) and homogenization pressure (500-700 bar)] toward two response variables (droplet size, polydispersity index) was studied using central composite design (CCD) coupled to RSM. RSM analysis showed that the experimental data could be fitted into a second-order polynomial model and the coefficients of multiple determination (R²) is 0.9115. The optimized formulation of NE consisted of 6.09 wt% mixed surfactant [Tween 80/Span 80 (63:37, wt)], 20 wt% glycerol as a co-solvent via homogenization pressure (500 bar). The optimized NE response values for droplet size and polydispersity index were 119.49nm and 0.286, respectively. The actual values of the formulated nanoemulsion were in good agreement with the predicted values obtained from RSM, thus the optimized compositions have the potential to be used as a nanoemulsion for cosmetic formulations.